Tropaeolaceae: A New Family Record for the Flora Of Saudi Arabia (Bangladesh Journal of Plant Taxonomy, 2022)
The family Tropaeolaceae was reported for the first time in Saudi Arabia. The new record (Tropaeolum majus L.) from the Tropaeolaceae family was found in damp and exposed semi-shaded habitats between roughly 1800 and 2132 m elevation in southwestern Saudi Arabia. Illustrations, photos, taxonomic description, distribution map, key and information about the habitat of the plant were given. This study suggests that the new record is an introduced alien plant into Saudi Arabia.Bangladesh J. Plant Taxon. 29(1): 79-84, 2022 (June)